ASSESSMENT DAN DIAGNOSIS DALAM KONSELING ADIKSI - Maulana, Ade Hilman; Yusup, Aldian; Fitrianingsih, Fitrianingsih (Mandalika: Jurnal Ilmu Pendidikan dan Bahasa, 2025)
Addiction has become a complex mental health issue with significant psychological, social, and cultural implications, particularly in developing countries such as Indonesia. Accurate assessment and diagnosis are essential components of addiction counseling, as they determine the effectiveness of intervention and rehabilitation programs. This study aims to examine the role of assessment and diagnostic processes in addiction counseling and to evaluate their relevance within the Indonesian socio-cultural context. The research employs a qualitative method using a library research approach by analyzing peer-reviewed journal articles, books, official guidelines, and reports related to addiction counseling, assessment, and diagnosis. Data were analyzed through content analysis to identify key themes, patterns, and gaps in existing literature. The findings indicate that comprehensive assessment methods—such as interviews, psychological testing, behavioral assessment, and self-monitoring—play a critical role in understanding clients’ conditions holistically. However, the study also reveals challenges in adapting international diagnostic frameworks, such as the DSM-5 and ICD-11, to local cultural values and social realities. This study concludes that culturally sensitive and contextually relevant assessment and diagnostic approaches are urgently needed to enhance the effectiveness of addiction counseling services in Indonesia.